2010
DOI: 10.1142/s0219649210002553
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Collaborative Tagging: An Analysis of Tag Vocabulary Application in Knowledge Representation, Discovery and Retrieval

Abstract: This study investigates the contribution of collaborative tagging to the design of user-driven vocabularies in knowledge management systems (KMS). Three metrics, tag growth, tag reuse, and tag discrimination, were used to examine the evolution of the tagging vocabulary of the knowledge management community of interest in CiteULike over a three-year period. Results indicate a steady decrease in the number of unique tags over the four years, suggesting an increasing stability in the community vocabulary over tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
4
2
Order By: Relevance
“…9 depicts, the value of the tag discrimination metric for the OSR Repository has been stabilized to 3,65 LOs/tag. This value is lower than the reported by Farooq et al (2007) CiteULike (4,47LOs /tags) and the reported by Makani & Spiteri (2010) value (4,11LOs/tags) in Calibrate Portal.…”
Section: Analysis Of Tag Discriminationcontrasting
confidence: 67%
See 2 more Smart Citations
“…9 depicts, the value of the tag discrimination metric for the OSR Repository has been stabilized to 3,65 LOs/tag. This value is lower than the reported by Farooq et al (2007) CiteULike (4,47LOs /tags) and the reported by Makani & Spiteri (2010) value (4,11LOs/tags) in Calibrate Portal.…”
Section: Analysis Of Tag Discriminationcontrasting
confidence: 67%
“…The value of the tag reuse metric has been stabilized to 1,797 users/tag. This value is higher than the reported by Farooq et al (2007) value in CiteULike (1,59 users/tag) and the reported by Vuorikari & Ochoa (2009) value (1,22 users/tags) in Calibrate Portal but still quite low if compared to the reported by Makani & Spiteri (2010) value in CiteULike knowledge management community (23 users/tag).…”
Section: Analysis Of Tag Reusecontrasting
confidence: 63%
See 1 more Smart Citation
“…While it has been demonstrated [42,43] that these approaches yield sets of terms that are fit for purpose, it is debatable whether or not the results may be labelled as “controlled vocabularies”, e.g., it has been shown [44] that these approaches are highly susceptible to the effects of user-bias. In contrast, our approach, where terms are drawn from a community-approved, expertly-composed text, yields a true controlled vocabulary.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Currently, publications are characterised using terms that are either arbitrarily selected by authors/editors or (semi-)automatically extracted from the content of the publication by software systems [ 41 ]. While it has been demonstrated [ 42 , 43 ] that these approaches yield sets of terms that are fit for purpose, it is debatable whether or not the results may be labelled as “controlled vocabularies”, e.g., it has been shown [ 44 ] that these approaches are highly susceptible to the effects of user-bias. In contrast, our approach, where terms are drawn from a community-approved, expertly-composed text, yields a true controlled vocabulary.…”
Section: Methods and Resultsmentioning
confidence: 99%